Quantifying acute changes in neurometabolism following blast-induced traumatic brain injury - Carly Norris; Justin Weatherbee; Susan F. Murphy; Pamela J. VandeVord (Neuroscience Research, 2024)
Brain health is largely dependent on the metabolic regulation of amino acids. Brain injuries, diseases, and disorders can be detected through alterations in free amino acid (FAA) concentrations; and thus, mapping the changes has high diagnostic potential. Common methods focus on optimizing neurotransmitter quantification; however, recent focus has expanded to investigate the roles of molecular precursors in brain metabolism. An isocratic method using high performance liquid chromatography with electrochemical cell detection was developed to quantify a wide range of molecular precursors and neurotransmitters: alanine, arginine, aspartate, serine, taurine, threonine, tyrosine, glycine, glutamate, glutamine, and γ-Aminobutyric acid (GABA) following traumatic brain injury. First, baseline concentrations were determined in the serum, cerebrospinal fluid, hippocampus, cortex, and cerebellum of naïve male Sprague Dawley rats. A subsequent study was performed investigating acute changes in FAA concentrations following blast-induced traumatic brain injury (bTBI). Molecular precursor associated FAAs decreased in concentration at 4 h after injury in both the cortex and hippocampus while those serving as neurotransmitters remained unchanged. In particular, the influence of oxidative stress on the observed changes within alanine and arginine pathways following bTBI should be further investigated to elucidate the full therapeutic potential of these molecular precursors at acute time points.